PENYULUHAN PROGRAM PHBS CUCI TANGAN DI SD NEGERI 106165 MARINDAL I DELI SERDANG - Sahat Sinaga; Lydia Br. Barus; Nurbaiti Br. Singarimbun; Defacto Firmawati Zega; Helen Anjelina Simanjuntak; Hermawan Purba (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The degree of public health can be seen from the level of health. Efforts to improve health can be done by implementing the Clean and Healthy Living Behavior hand washing program in the school environment. Hand washing is carried out with the aim of being clean and can have an impact on preventing infectious diseases such as infections that cause diarrhea, Covid-19, intestinal worms, respiratory infections and other infections. So it is necessary to carry out community service activities in the form of Clean and Healthy Living Behavior counseling to 28 class II students at SD Negeri 106165 Marindal I Deli Serdang Regency as one of the efforts to prevent the spread of infectious diseases in the school environment which will later have an impact on the home and in the community. The activity method is carried out by lectures, questions and answers, demonstrations and evaluations. The results of the activity showed that there was an increase in students' knowledge about hand washing, the impact of not washing hands and how to wash hands properly and correctly. There are several factors that support the implementation of Clean and Healthy Living Behavior hand washing in schools, namely; the existence of teacher support, peer support, and hygiene facilities in washing hands.